PENGARUH HIPERGLEMI TERHADAP PERAN SITOSKELETON (CYTOSKELETON) SEBAGAI JALUR TRANSDUKSI SIGNAL (SIGNAL TRANSDUCTION) - Rudijanto, Achmad; Kalim, Handono (journal of internal medicine, 2012)
Intracellular signal transduction occurs through cascades of reactions involving dozens of proteins that transmit signals from the cell surface, through a crowded cellular environment filled with organelles and a filamentous cytoskeleton, to specific target. For most characterized signal transduction pathway, the initial signaling event and the end point are well known. In order to fully understand intracellular signal transduction, it is essential to know the intermediate signaling molecules and to understand how information flows from one to the next. The cytoskeleton , an interconnected assembly of actin (microfilament), intermediate filament and microtubule networks that extend throughout the entire cell, is involved in intracellular signal transduction. Individual proteins of the cytoskeleton might participate directly in signal transduction by linking two or more signaling protein and might also provide a macromolecular scaffold, which spatially organizes components of a signal transduction cascade. Diabetes mellitus is an increasingly common disease. Absolute or relative deficiencies of insulin are common in this disease. Insulin has been suggested to play a key regulatory role in the functional organization of actin filaments. The microtubules are also the targets of insulin. A chronic insulin deficiency may could lead to impairment in the organization of the cytoskeleton. This could entail a compromised or slower action of some activated enzymes in cells, affect to intracellular signal transduction.
Keywords: hyperglycemia, cytoskeleton, signal transduction